FACULTY AND STUDENTS' PERCEPTION ABOUT APTITUDE OF PROFESSIONALISM IN ADMISSION PROCESS OF MEDICAL COLLEGE - Waheed, Gulfreen; Mengal, Mohammad Amin; Shah, Syed Shaukat Ali; Sheikh, Abdul Waheed (Journal of Ayub Medical College Abbottabad, 2011)
Background: Historically, knowledge and skill were of prime focus in medical education, where as professionalism was perceived as an attribute to be acquired during their MBBS studies. In the past decade, trends have changed and graduating medical students are expected to competently deliver care in a professional manner. The selection of applicants with professional attributes at the time of admission is a stepping stone for the formation of a good doctor. This study was conducted to determine the students' and faculty's perception about aptitude of professionalism in the admission process in our setting. Methods: In this descriptive cross-sectional study an interactive/scenario-based conversation regarding institutional values, contribute to personal reflection of what will be expected of them in the medical profession and inclusion of such discussion in admission process was made to assess the aptitude of Professionalism of 100 students and 100 faculty members of Avicenna Medical College Lahore. After this conversation the questionnaires were filled by both the groups to record their responses on the aptitude of professionalism. The data was analysed to determine the response patterns of both the groups by using Pearson Chi-Square analysis through crosstabs. All analyses were carried out using SPSS-18. Results: The response of students to professionalism discussion was more positively influenced (91%) compared to the faculty (59%), (p<0.05). The students agreed that such scenarios do indicate what our institution values in its students and contribute to personal reflection of what will be expected of them in the medical profession. However, faculty agreed more (85%) than the students (67%) for inclusion of such scenarios in admission process, p<0.05. Conclusions: Medical Colleges should include some form of assessment regarding aptitude of professionalism in the admission process to identify future medical students' capacity for professional behaviour. Future studies are needed to determine innovative interview strategies for this purpose. Keywords: Students' perception, professionalism, admission process, medical colleges